PSYCHOLOGICAL AND ORGANIZATIONAL-PEDAGOGICAL FOUNDATIONS OF TRAINING PSYCHOLOGISTS IN THE HIGHER EDUCATION SYSTEM (Web of Teachers: Inderscience Research, 2025)
Some information is provided on the organizational and pedagogical foundations of the cognitive-psychological process in ensuring the continuity of improving the training of psychologists-specialists in the higher education system. Taking this into account, three specific aspects of leading the training of psychologists-specialists in the higher education system are highlighted.